2006
DOI: 10.1007/s10709-006-6248-4
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of pBuM–2 satellite DNA sequences among geographically isolated Drosophila gouveai populations from Brazil

Abstract: In this study, we have compared 34 repetition units of pBuM-2 satellite DNA of individuals from six isolated populations of Drosophila gouveai, a cactophilic member of Drosophila buzzatii cluster (repleta group). In contrast to the results of previous morphological and molecular data, which suggest differentiation among the D. gouveai populations, the sequences and the cluster analysis of pBuM-2 monomers showed that this repetitive element is highly conserved among the six D. gouveai populations (97.8% similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(76 reference statements)
3
8
0
1
Order By: Relevance
“…Our analyses suggest that no specific nucleotide substitutions or indels were identified in MspI satDNA monomers, which could discriminate single populations or groups of geographically close populations at the scale of the Peninsula of Setúbal. Such a lack of intraspecific molecular structure in satDNA sequences has been observed in several Drosophila species (Kuhn and Sene, 2004;Franco et al, 2006), and was suggested to arise due to the combination of both past and current gene flow events among populations and independent homogenization mechanisms favoring monomers shared among the populations (Kuhn and Sene, 2004;Franco et al, 2010). Considering the very recent invasion of Portugal by B. xylophilus (Mota et al, 1999), and the limited dispersion capacity of the nematode, it is very unlikely that a significant amount of gene flow has occurred within the investigated area.…”
Section: Discussionmentioning
confidence: 74%
“…Our analyses suggest that no specific nucleotide substitutions or indels were identified in MspI satDNA monomers, which could discriminate single populations or groups of geographically close populations at the scale of the Peninsula of Setúbal. Such a lack of intraspecific molecular structure in satDNA sequences has been observed in several Drosophila species (Kuhn and Sene, 2004;Franco et al, 2006), and was suggested to arise due to the combination of both past and current gene flow events among populations and independent homogenization mechanisms favoring monomers shared among the populations (Kuhn and Sene, 2004;Franco et al, 2010). Considering the very recent invasion of Portugal by B. xylophilus (Mota et al, 1999), and the limited dispersion capacity of the nematode, it is very unlikely that a significant amount of gene flow has occurred within the investigated area.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast with the DBC-150 family, the pBuM subfamilies are slightly AT-rich (66% on average) N=number of analyzed repeats. Data from a Kuhn & Sene (2005); b Kuhn et al (2003) and c Franco et al (2006); d Kuhn & Sene (2004). and present lower levels of sequence variability, from 1.9% to 5.0%.…”
Section: Satellite Dna Characterizationmentioning
confidence: 90%
“…However, the pBuM-1 and pBuM-2 evolutionarily related satDNA subfamilies from the D. buzzatii species cluster (repleta group) showed different sequence variability, indicating a slower rate of evolution of the pBuM-2 subfamily (Kuhn and Sene, 2005). This subfamily even showed high sequence conservation among geographically isolated populations from D. gouveai, a species included in this group (De Franco et al, 2006).…”
Section: Changes In Sequence Variabilitymentioning
confidence: 98%